Biolighted Nanotorch Capable of Systemic Self-Delivery and Diagnostic Imaging - Singh, Ajay; Seo, Young Hun; Lim, Chang-Keun; Koh, Joonseok; Jang, Woo-Dong; Kwon, Ick Chan; Kim, Sehoon (AMER CHEMICAL SOC, 2015)
Sensitive imaging of inflammation with a background-free chemiluminescence (CL) signal has great potential as a clinically relevant way of early diagnosis for various inflammatory diseases. However, to date, its feasibility has been limitedly demonstrated in vivo with locally induced inflammation models by in situ injection of a probes. To enable systemic disease targeting and imaging by intravenous administration of CL probes, hurdles need to be overcome such as weak CL emission, short glowing duration, or inability of long blood circulation. Here, we report a CL nanoprobe (BioNT) that surmounted such limitations to perform precise identification of inflammation by systemic self-delivery to the pathological tissues. This BioNT probe was engineered by physical nanointegration of multiple kinds of functional molecules into the ultrafine nanoreactor structure (similar to 15 nm in size) that combines solid-state fluorescence-induced enhanced peroxalate CL and built-in machinery to control the intraparticle kinetics of CL reaction. Upon intravenous injection into a normal mouse, BioNT showed facile blood circulation and generated a self-lighted strong CL torchlight throughout the whole body owing to the tiny colloidal structure with an antifouling surface as well as high CL sensitivity toward endogenous biological hydrogen peroxide (H2O2). In mouse models of local and systemic inflammations, blood-injected BioNT visualized precise locations of inflamed tissues with dual selectivity (selective probe accumulation and selective CL reaction with H2O2 overproduced by inflammation). Even a tumor model that demands a long blood circulation time for targeting (>3 h) could be accurately identified by persistent signaling from the kinetics-tailored BioNT with a 65-fold slowed CL decay rate. We also show that BioNT exhibits no apparent toxicity, thus holding potential for high-contrast diagnostic imaging.
Keywords: AGGREGATION-ENHANCED FLUORESCENCE; INDUCED EMISSION CHARACTERISTICS; MODIFIED SILICA NANOPARTICLES; HYDROGEN-PEROXIDE; CHEMILUMINESCENCE; NANOPROBES; CELL